Penerapan Transparansi Dan Akuntabilitas Pengelolaan Alokasi Dana Desa Di Desa Kupa-Kupa Selatan Kecamatan Tobelo Selatan Kabupaten Halmahera Utara - Miseri Cordia Tongotongo; Jantje J Tinangon; Robert Lambey (Universitas Sam Ratulangi, 2023)
The goal of this study is to learn the application of transparency and accountability in the process of managing the Village Fund Allocation (ADD) in Kupa-Kupa Selatan Village based on the Minister of Home Affairs Regulation Nomor 20 of 2018 concerning Village Financial Management. This study uses a type of qualitative research with a descriptive approach, where researchers go directly to the field to observe and understand the condition of the object and examine the problems experienced, as well as gather verbal or written data that is descriptive. From the results of this study, it can be concluded that the level of transparency and accountability of the Kupa-Kupa Selatan Village Government is still relatively low because there isn't enough room human resources in presenting accountability reports so that this affects the level of transparency and accountability which is the principle of Permendagri Nomor 20 of 2018 concerning Village Financial Management. To ensure the creation of good governance, especially in increasing transparency and accountability, it is necessary to have solid cooperation and synergy with the village, district, and community governments. The process of training/debriefing, mentoring, control and community participation are the main keys to the creation of good governance.